Rainfall Risk and Religious Membership in the Late Nineteenth-Century United States - Philipp Ager; Antonio Ciccone (University of Mannheim, Department of Economics, 2014)
Building on the idea that religious communities provide mutual insurance against some idiosyncratic risks, we argue that religious membership is more valuable in societies exposed to greater common risk. In our empirical analysis we exploit rainfall risk as a source of common economic risk in the nineteenth-century United States and show that religious communities were larger in counties where they faced greater rainfall risk. The link between rainfall risk and the size of religious communities is stronger in counties that were more agricultural, that had lower population densities, or that were exposed to greater rainfall risk during the growing season.
urn:nbn:de:bsz:180-madoc-368488
Keywords: 330; Religious community size; agricultural risk; informal insurance